History book Class 7 understanding History class 7 - Ismat riaz; Ismat Riaz (karachi Oxford, 2024)
Book 2 for grade 7 explores the Medieval Ages and the impact of Islamic empires and the Crusades. It carries the subcontinent's history forward from the ...
Keywords: Text book